Mode of Attack on Orchardgrass Leaf Blades by Rumen Protozoa - Akin, Danny E. (1979)
Leaf blade sections of orchardgrass were incubated with rumen fluid and examined by scanning and transmission electron microscopy for the mode of attack on tissues by rumen protozoa. Rumen protozoa resembling Epidinium ecaudatum from caudatum degraded forage tissue in diluted, whole rumen fluid suspensions of microbes containing 1.6 mg of streptomycin per ml, which inhibited bacterial fiber-digesting activity. Cell walls of mesophyll, parenchyma bundle sheath, and epidermis became swollen and frayed to reveal a microfibrillar network and loss of electron density, indicating partial degradation. Then the protozoa ingested whole cells and fragments of cell walls with the aid of their cilia. Plant cells with partially degraded walls as well as chloroplasts without walls were present within the protozoa. These entodiniomorphs digested orchardgrass leaves by partially degrading the plant cell walls apparently by extracellular enzymes and then ingestion of the plant cells and cell wall fragments.